BOOK REVIEW OF JOHN GRISHAM’S SKIPPING CHRISTMAS - Taqwa, Syambara Bella (LANTERN (Journal on English Language, Culture and Literature), 2015)
This book review is arranged with the purpose to show the strengths and weaknesses of a novel entitled Skipping Christmas, authored by an American author, John Grisham. This novel tells a story of the Kranks couple who wanted to skip Christmas to go on a cruise instead. This novel is the only comedy novel that is written by John Grisham who is a well-known thriller author. The strengths of the novels are the moral value of the novel, the cover design, and the greatness of the author’s name. This novel tells what Christmas is about. The greatness of the author’s name and the cover design are very powerful to attract people to buy and read the novel. The weaknesses of the novels are the dictions and the naratology of the novel that is too detailed. The author tends to use difficult words to tell the story. There are too many details in the novel to bore the readers. The main aim of this book review is to give a picture about the novel and a reference for the readers before reading the whole novel.